Review of soil-water characteristic curve equations - Rahardjo, Harianto (2011)
Practical applications of unsaturated soil mechanics still lag behind the state-of-the-art knowledge. The main stumbling block is the time-consuming processes involved in the measurement of the unsaturated soil parameters required for the constitutive models. Recent research has shown that the soil-water characteristic curves of a soil can be used in the establishment of a number of the unsaturated soil parameters. In many applications it has become obvious that a satisfactory equation for describing the soil-water characteristic curve will simplify the determination of the soil parameters. Over the years a number of equations have been suggested. Most of these equations have limited success depending on soil types. This paper evaluates the more popular equations that have been suggested and shows that all the equations can be derived from a single generic form. One equation has been identified that performs very well for all soil types. If this equation is in common usage, useful databases on unsaturated soil parameters can be more easily established for practical applications of unsaturated soil mechanics.